Trends and Research Gaps in Receptive Language Acquisition of Seven-Year-Olds Children with Speech Delay - Nursani; Nuraini Kasman; Jumiati; Indriani H. Ismail (Raja Zulkarnain Education Foundation, 2026)
Receptive language development is a fundamental aspect of children’s learning and communication processes, yet many seven-year-olds experience speech delay that impacts their academic and social abilities. Although numerous studies have been conducted, the direction and focus of research in this field remain fragmented and lack strong thematic consistency. This study aims to identify trends, main themes, and research gaps in scientific literature related to receptive language acquisition in seven-year-olds with speech delay through a Systematic Literature Review (SLR) and bibliometric analysis approach. Data were obtained from the Scopus database using specific keyword combinations following the PRISMA protocol, then analyzed using VOSviewer and NVivo software to generate thematic network visualizations and research gap word clouds. The analysis results indicate that publications fluctuated with a peak in 2021, dominated by contributions from the United States and institutions such as Boston University and the University of Wisconsin-Madison. Three main thematic clusters were identified, including early language development, diagnosis and intervention, and socio-linguistic context. Research gaps were found in the lack of studies specifically targeting seven-year-olds, limited longitudinal research, and insufficient exploration of technology-based interventions. This study concludes that there is a need for research focus on specific age groups, strengthening longitudinal methodologies, expanding cross-country collaboration, and integrating technology in interventions to improve the effectiveness of receptive language disorder treatment in children.